From barbed wire to genetically modified seeds. An analysis of agriculture in the Pampas region in the light of Argentinean rural journals (2007-2009) - Hendel, Verónica (Nómadas. Critical Journal of Social and Juridical Science, 2015)
Genetically modified seeds can be considered to be the “colonizing crop” of the newly born century. Going back into Argentina’s history and culture, we may observe that the wire operated mainly over territory, establishing boundaries, creating capitals and expelling ‘gauchos’, and the tractor affected the “human element” and the relationship between the latter and its surroundings in a context marked by the emergency of a series of discourses related to labour and general wealth. The goal of genetically modified seeds’ intervention may be considered as life itself, the configuration of vegetal and animal organisms. In this case, technology expels life from the rural area and redefines the boundaries between human, vegetal and animal, wild and civilized, country and city, man and machine. This is the effect of modernization that we seek to analyze. In order to do so, we will place ourselves in the Argentinean Pampas and take the concept of landscape as a starting point (Mitchell, 2002; Cosgrove, 2006; Andermann, 2000);this means we will use this notion to analyze a series of writings that have been published in the rural magazine of the most popular Argentina’s newspaper during the last years.
Keywords: genetically modified seeds; Pampas region; landscape